Numerical analysis of inhomogeneous Schottky diode with discrete barrier height patches. Issue 6 (2nd June 2016) - Kaushal, Priyanka; Chand, Subhash
ABSTRACT: The potential profile inside the semiconductor at the metal–semiconductor contact is simulated by numerically solving the Poisson equation and the drift diffusion equations for inhomogeneous Schottky diode. From the simulated potential and the electron and hole concentrations, the drift-diffusion current as a function of bias is calculated. The simulation is carried out for various distribution patterns of barrier height patches at the metal–semiconductor contact to study the effect of barrier inhomogeneities on the Schottky diode parameters, namely barrier height and ideality factor and their temperature dependence. It is found that barrier height decreases and ideality factor increases with increase in the deviation of discrete barrier height patches in the distribution. The resulting barrier parameters are studied to understand the effect of barrier inhomogeneities on the current–voltage characteristics of inhomogeneous Schottky contact.